Ecoprint Training as an Innovative Environment-Based Chemistry Learning Program for Students of SMAN 13 Pontianak - Rody Putra Sartika; Masriani Masriani; Rini Muharini; Rachmat Sahputra; Lukman Hadi; Aldi Tobing; Muhammad Rafif; Medardus Josua Petrus Tosang; Adila Bilqis (STKIP Singkawang, 2026)
Chemistry learning in secondary schools is still predominantly theoretical, limiting students' opportunities to connect scientific concepts with contextual and environment-based learning experiences. As a result, the use of the surrounding environment as a learning resource, as well as the development of creativity, environmental awareness, and twenty-first-century skills, has not been fully optimized. This community service program aimed to implement ecoprint training as an innovative approach to environment-based chemistry learning and to evaluate its impact on students' knowledge and skills, environmental awareness, creativity and critical thinking, green entrepreneurship, and collaborative learning. The program involved 171 tenth-grade students of SMAN 13 Pontianak and employed a hands-on training approach consisting of instructional sessions, ecoprint practice using locally available natural materials, reflective discussions, and post-activity evaluation using a five-point Likert-scale questionnaire. Data were analyzed using descriptive quantitative methods based on the mean scores of each evaluation aspect. The results indicated that all assessed aspects achieved good to very good categories, including knowledge and skills (3.75), environmental awareness (4.14), creativity and critical thinking (3.96), green entrepreneurship (3.91), and collaborative learning and partnership (4.04). In addition, the program produced dozens of naturally dyed ecoprint works collaboratively created by the participants as tangible outcomes of practice-based learning. These findings demonstrate that ecoprint training not only enhances students' understanding of chemistry concepts through experiential learning but also strengthens environmental literacy, creativity, collaboration, and awareness of sustainable entrepreneurship. This program offers an innovative environment-based chemistry learning approach that integrates scientific concepts, local natural resources, and sustainability values, providing a replicable model to support the implementation of Education for Sustainable Development (ESD) in schools.Pelatihan Ecoprint sebagai Inovasi Pembelajaran Kimia Berbasis Lingkungan bagi Siswa SMAN 13 PontianakABSTRAKPembelajaran kimia di sekolah menengah masih didominasi oleh pendekatan teoretis sehingga belum sepenuhnya menghubungkan konsep sains dengan pengalaman belajar yang kontekstual dan berbasis lingkungan. Kondisi ini menyebabkan pemanfaatan lingkungan sebagai sumber belajar serta pengembangan kreativitas, kepedulian lingkungan, dan keterampilan abad ke-21 belum optimal. Kegiatan Pengabdian kepada Masyarakat ini bertujuan mengimplementasikan pelatihan ecoprint sebagai pendekatan inovatif dalam pembelajaran kimia berbasis lingkungan serta mengevaluasi dampaknya terhadap pengetahuan dan keterampilan, kesadaran lingkungan, kreativitas dan berpikir kritis, green entrepreneurship, serta pembelajaran kolaboratif siswa. Kegiatan melibatkan 171 siswa kelas X SMAN 13 Pontianak melalui pendekatan hands-on training yang dipadukan dengan penyampaian materi, praktik pembuatan ecoprint menggunakan bahan alami lokal, diskusi reflektif, dan evaluasi menggunakan angket skala Likert lima tingkat. Data dianalisis secara deskriptif kuantitatif berdasarkan nilai rata-rata setiap aspek penilaian. Hasil menunjukkan bahwa seluruh aspek berada pada kategori baik hingga sangat baik, yaitu pengetahuan dan keterampilan (3,75), kesadaran lingkungan (4,14), kreativitas dan berpikir kritis (3,96), green entrepreneurship (3,91), serta kemitraan dan pembelajaran kolaboratif (4,04). Kegiatan juga menghasilkan puluhan karya ecoprint berbahan alami sebagai luaran pembelajaran berbasis praktik. Temuan ini menunjukkan bahwa ecoprint efektif sebagai pendekatan pembelajaran kimia berbasis lingkungan yang mengintegrasikan konsep sains, pemanfaatan sumber daya lokal, dan nilai keberlanjutan, serta berpotensi direplikasi untuk mendukung implementasi Education for Sustainable Development (ESD).Kata Kunci :Ecoprint; Pembelajaran Berbasis Lingkungan; Pendidikan Kimia; Pengabdian Masyarakat